Isolation and characterization of PLA-degrading bacteria from landfill soil at mesophilic temperature - J. C., Jalani; Zatul Iffah, Mohd Arshad; Shalyda, Md Shaarani; Rohaida, Che Man; Siti Kholijah, Abdul Mudalip; Siti Zubaidah, Sulaiman (IOP Publishing, 2020)
This study aimed to isolate and characterize polylactic acid (PLA) degrading bacteria present in landfill soils located in Pekan, Pahang. The conducted study involves collecting four soil samples from four different sources and stored at room temperature before undergoing serial dilution from dilution factor (DF) 10−1 until dilution factor 10−10. Characterization of bacteria via Gram staining was done only on isolates (69 colony) with DF 10-6 until DF 10-10 but only 13 isolates from plate with DF 10-8 and 10-10 were re-streaked to obtain single colony. The single colony obtained were further characterized for their morphological characteristics and tested for presence of protease enzyme by streaking the colony on skim milk agar which resulted with only four (A10K, A10B, B8A and D10A) showing positive presence of protease enzyme. The four plates were tested for catalase using 3%(v/v) hydrogen peroxide and all resulted with vigorous bubbling which indicate positive catalase enzyme. Relative enzyme activity was calculated for all four bacteria through observation of halo zones on skim milk agar, and isolate A10B shows the highest relative enzyme activity with 3.86, and thus showing potential to accelerate the degradation of PLA at mesophilic temperature. Therefore, in this study, it is proven to be possible to isolate bacteria that can degrade PLA at mesophilic temperature from landfill soil.